KERJASAMA ANTARA MASYARAKAT TIONGHOA DENGAN MASYARAKAT LOKAL DI BAGAN BATU KECAMATAN BAGAN SINEMBAH KABUPATEN ROKAN HILI - Selly Devi Tambunan; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research was conducted in Bagan Batu, Bagan Sinembah, Kabupaten Rokan Hilir. The problem studied was the form of cooperation carried out by the Chinese community with the local community in Bagan Batu and how the adaptation between the Chinese community and the local community in Bagan Batu. The purpose of this study was to find out how the form of cooperation carried out by the Chinese community with the local community in Bagan Batu and to find out how the adaptation between the people of Tionghoa and the local community in Bagan Batu. The sample in this study is 9 (nine) where the local community 5 (five) people and 4 (four) Chinese communities. In this study researchers used the theory of cooperation and adaptation. The author uses descrivtive qualitative research method, namely, describes the phenomena that occur in the field according to the actual situation with the procedure of problem solving based on circumstances as it is. Simple random sampling writing technique is a data collection technique suitable for this study, where Simple Random Sampling is technique chosen randomly, this method can be taken if the analysis of research tends to be descrivtive or general in nature. From the results of this study the form of cooperation in Bagan Batu is in the form of cooperation in the field of economics, especially in the field of trade and social field.Keywords: Cooperation, Chinese Community, Local Community